Contributos da discussão matemática para a aprendizagem dos números racionais - Alves, Rosa (2020)
This paper arises from a study that aims to understand how to perform the learning of rational numbers by 5th grade students when involved in an educational experience that focuses on inquiry based approach to mathematics teaching, given a culture of discussion. The study follows a qualitative and interpretative methodology, taking the first author the teacher role and simultaneously the investigator one. The data collection includes: participant observation, audio recordings of collective discussions, interviews, questionnaires and written productions of students, final test and field notes. The study results show that students adhered to a culture of discussion in mathematics classroom, developing diacussion skills (questioning, answering, explaining, listening, as well as other actions related to the initiation of dialogue or reflection on the what was presented). Furthermore, students generally show to understand the concept of rational number and their representations, transforming them according to specific situations, which facilitates the completion of tasks about to the comparison and sorting, as well as understanding the addition / subtraction algorithm of rational numbers represented by fractions.